Parasitoid–host association in invaded communities - Duan, Jian J; Quinn, Nicole F; Weber, Donald C (Current opinion in insect science, 2024)
In nature, most parasitoids attack more than one host species, and nearly all hosts are attacked by several species of parasitoids. This opens many potential opportunities for interactions of invasive species with native parasitoid–host association networks in invaded communities. Despite this, few studies have examined the direct and indirect impacts of biological invasion on parasitoid–host associations. This review examines what is known of these relationships from the most recent literature and suggests future research priorities. We conclude that parasitoid–host association networks in invaded communities are complex, dynamic, and subject to trophic intrusions from invasive plants, herbivores, plant pathogens, parasitoids, and hyperparasitoids. Future studies should take a holistic systems approach to understanding the impact of biological invasion and its consequences in shaping community structure through altering existing native, coevolved parasitoid–host association networks. ●In nature, parasitoid–host associations are complex and do not exist in isolation.●These networks are subject to intrusion by invasive species at all trophic levels.●Impact of invasive species varies with species and attributes of invaded ecosystems.●Holistic approaches are needed to understand invasion impacts on parasitoid–host associations.